Answer:
= 3n + 3
Step-by-step explanation:
The sequence is arithmetic with explicit formula
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
From the recursive formula
a₁ = 6 and d = 3 [ the constant being added to A(n - 1) ] , then
= 6 + 3(n - 1) = 6 + 3n - 3 = 3n + 3
Answer:
x= 6
Step-by-step explanation:
since both sides equal the same amount..
5x-7=3x+5
you plug it in through a calculator or work it out. if you dont know how to work it out, try the app <u>photomath</u><u>,</u><u> </u>it shows you solving steps :))
Answer:
X = 4
Step-by-step explanation:
5x + 3 = 23
Subtract 3 from both sides: 5x = 20
Divide both sides by 5: x = 4
Answer:
Craig must be rich LOL cuz It says its 1/20 of his paycheck each month so u have to multiply by 20
Step-by-step explanation:
720*20 = 14440
Answer:
19
Step-by-step explanation:
1-(-18)
=1+18
=19